The Effectiveness of Training Anthropometry using Cards to Increase Adolescents' Knowledge and Skill - Vivi Oktavia; Siti Budi Utami; Almira Sitasari; Tri Siswati (Ficco Scientific Corner, 2025)
Background: Adolescents in Indonesia face the triple burden of malnutrition due to low nutritional literacy. This study evaluates the impact of Learning Cards (in bahasa: Kartu Belajar or Kejar) in improving anthropometric knowledge and skills among adolescents. Methods: This was a pre-experimental, single-group pre-test post-test design was conducted in Giripanggung Village, Tepus, Gunung Kidul, Yogyakarta, Indonesia in 2023. Fifty adolescents, aged 11-19 years, participated in a three-day offline training covering weight, height, and mid-upper arm circumference measurements. Data were collected at three points (pre-test, post-test 1, and post-test 2) and analyzed using tests. Results: Adolescents' knowledge significantly improved from a pre-test mean score of 54.7 ± 11.8 to 79.7 ± 11.9 in post-test 1 (p < 0.05). While post-test 2 showed a slight decline (77.6 ± 12.5), knowledge remained significantly higher than baseline (p < 0.05). Anthropometric skills also increased substantially, with weight measurement scores rising from 51.3 ± 21.5 (pre-test) to 85.3 ± 13.7 (post-test 1, p < 0.05). Although post-test 2 showed a decline (75.2 ± 15.4), the scores remained higher than the pre-test (p < 0.05). Conclusions: Training using Kejar effectively enhances adolescents' knowledge and skills in anthropometry. These findings suggest that expanding the use of Kejar media to other communities could Improve adolescent nutrition literacy at a national level.